PENERAPAN METODE “ROLE PLAYING” MELALUI MEDIA PEMBELAJARAN DIGITAL DI PERGURUAN TINGGI - Ibnatur Husnul, Nisak Ruwah; Friska, Yuliana; Fitriyah (QATHRUNÂ, 2024)
This research aims to examine the application of the "role playing" method through digital learning media in English and Mathematics courses at universities. This type of research is classroom action research carried out to improve students' communication skills and understanding of mathematical concepts. The target of this research is second semester students taking English and Mathematics courses at a university in Indonesia. The subjects of this research are lecturers and students who are directly involved in the learning process, while the research object is the application of the "role playing" method and digital learning media. The population in this study were all students who took these two courses, and the sample was taken by purposive sampling of 60 students. Data collection techniques include observation, test and questionnaires to obtain qualitative and quantitative data. The data obtained were analyzed using descriptive and inferential analysis techniques. The research results show that the application of the "role playing" method through digital learning media significantly improves communication skills in English and understanding of concepts in Mathematics. Students also show increased learning motivation and active participation in class. Implementation of this method is recommended to enrich learning strategies in higher education.